Identification and functional characterization of lncRNAs involved in human monocyte-to-macrophage differentiation - Christy Montano; Sergio Covarrubias; Eric Malekos; Sol Katzman; Susan Carpenter (RNA Biology)
Although long noncoding RNAs (lncRNAs) constitute the majority of the human transcriptome, the functional roles of most remain elusive. While protein-coding genes in macrophage biology have been extensively studied, the contribution of lncRNAs in this context is poorly understood. Given the vast number of lncRNAs (>20,000), identifying candidates for functional characterization poses a significant challenge. Here, we present two complementary approaches to pinpoint and investigate lncRNAs involved in monocyte-to-macrophage differentiation: RNA-seq for functional inference and a high-throughput functional screen. These strategies enabled us to identify four lncRNA regulators of monocyte differentiation: lincRNA-JADE1, lincRNA-ANXA3, GATA2-AS1, and PPP2R5C-AS1. Preliminary insights suggest these lncRNAs may act in cis through neighbouring protein-coding genes, although their precise mechanisms remain to be elucidated. We further discuss the strengths and weaknesses of these methodologies, along with validation pipelines crucial for establishing lncRNA functionality.